Bridging the Gap: Managing Dual Assurance Levels in OpenID Connect - Silva, Brendon Vicente R.; Schardong, Frederico; Custódio, Ricardo F. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2024)
This paper introduces and addresses challenges in managing electronic identity’s Level of Assurance (LoA), which has two types: LoA of authentication and LoA of identity. We explore different technical specifications, protocols, and concrete identity providers’ strategies for managing these two levels of assurance, highlighting the implications of protocols supporting only a single LoA instead of two. An extension to the OpenID Connect protocol is proposed to support both LoA types, instituting a new claim, the Identity Context Class Reference (ICR). This approach ensures compatibility and versatility with existing technical specifications.